ANALISIS ISI TINGKAT KEBERIMBANGAN BERITA RUBRIK NEWS DAN SHOWBIZ YANG DISAJIKAN DALAM PORTAL BERITA LINE TODAY - Tiara Astra Parahita; Turnomo Rahardjo (Interaksi Online, 2019)
The digitalization of media has simplified the process of consuming news by society. One example of digitalization of media is LINE Today which provides access to information for society through news feed. LINE Today as news aggregator compiles various news content from several news portals. Ideally, LINE Today is supposed to apply gatekeeping which include validation level, accuracy, and news balancing. However LINE Today is frequently found to abandon validity of news source and balancing news to provide news as soon as possible. Thus this research aims to find news balance level in LINE Today as news aggregator by using descriptive quantitative analysis and probability sampling purposive technique. The number of sample as many as 50 news article are obtained from LINE Today which consist of five online news portal. They are Suara.com, Kompas.com, VIVA.co.id, Liputan6.com and Kumparan.com. This study found that news contents in LINE Today apply news balance at different levels. News balance is applied gradually in the news updates. Furthermore, observation of Ahmad Dhani’s hate speech verdict coverage in LINE Today is found biased. The result found that only slant element is applied in the news from total three element of news balance level. This is proven by using one-sided news coverage (source bias) which show in selection of opposing and supporting sources portion in the news.